Congenital anatomical malformation at birth in Western Regional Hospital, Pokhara, Nepal - Sharma, I; Rijal, BT; Thapa, SB; Poudel, I (Journal of Universal College of Medical Sciences, 2014)
BACKGROUND: Congenital anomalies are any abnormality present at birth, either structural or functional, which may have been inherited genetically, acquired during gestation, or inflicted during parturition. There has not been much studies related to the congenital anomalies in Nepal. METHODOLOGY: One year hospital based review study was conducted to find out the incidence, magnitude of congenital malformation and to know the specific involvement of anatomical structures among babies born at Western Regional Hospital, Pokhara, Nepal. RESULTS: Of 10013 deliveries during the period of 1 year, total number of live birth was 98.82% (9895). Out of 9895 of total live births with any form of conginital anomolies was found amongst 0.42% (42) children, congenital anomalies were ranging from minor to major, single to multiple systems. Musculoskeletal anomalies accounted for the maximum of 57.1% followed by genitourinary anomaly 14.3%. Nervous system anomaly was seen in 11.9% and few cases of gastrointestinal system anomaly and anomalies of the sense organs. CONCLUSION: Incidence of congenital anatomical malformations at birth at Western Regional Hospital, Pokhara was found to be 0.42%. DOI: http://dx.doi.org/10.3126/jucms.v1i4.9572 Journal of Universal College of Medical Sciences (2013) Vol.1 No.04: 37-40